Development of steady state compact fusion neutron sources : final report of a coordinated research project. (IAEA-TECDOC, 2022)
"Fusion neutron sources have many important practical uses, such as irradiation testing of materials and components, facilitating the production of various isotopes such as tritium, driving subcritical cores, characterizing spent nuclear fuel, and manufacturing medical isotopes. All these applications can be potentially improved by achieving higher neutron yields and fluxes in compact fusion neutron sources (CFNSs). This publication is a compilation arising from an IAEA coordinated research project on this topic and presents the project's main results and findings with the aim of supporting stakeholders in the development of CFNSs in the transition from conceptual to engineering design."--Publisher's description.